Existe diferença na atividade eletromiográfica dos músculos mastigatórios entre indivíduos com e sem disfunção temporomandibular? revisão sistemática e metanálise - Barros, Bruna Massaroto (2018)
Introduction: Different methods of analysis have been used as a means of assessing temporomandibular dysfunction (TMD). However, it is still unclear in the literature whether this dysfunction also reflects the electromyographic (EMG) activity of the masticatory muscles. Objective: To verify if the DTM changes the EMG activity of the masseter muscles and the right and left anterior temporal muscles. Methods: This systematic review was performed according to the guidelines of the Systematic Reviews and Meta-Analysis Preferential Items (PRISMA), with sources that have allowed the comparative analysis of the EMG activity of the right and left anterior and temporal masseters among patients with TMD and healthy individuals, produced between 1990 and 2018, written in English, Portuguese or Spanish and collected in PubMed, Science Direct, Lilacs. Two independent reviewers verified the quality of the studies by means of a punctuated checklist containing general items according to STROBE and the International Society of Electrophysiology and Kinesiology (ISEK) guidelines. Results: Of the total of 979 articles, articles on clinical cases, articles that did not mention frequency of sampling and that did not use surface electrodes were excluded, those that did not report the frequency of sampling, articles of reproducibility, those that did not treat of the masseter and temporal muscles, those that dealt with arthrosis and degeneration, and those performed only with patients with TMD without a group of normal individuals. Once these exclusion criteria were met, twelve articles remained in this review. Nine studies presented good methodological quality and low risk of bias. Two studies allowed the combined analysis of the data to perform the meta-analysis, after calculating the mean difference and the confidence interval (CI: 95%). Conclusion: In this systematic review it was not possible to find evidence that TMD changes the EMG activity of the right and left anterior and temporal masseter muscles. However, the results of this review allowed the suggestion of a favorable protocol for the analysis of TMD.